Giant memory window performance and low power consumption of hexagonal boron nitride monolayer atomristor - Sung Jin Yang; Yu-Rim Jeon; Dongyoon Kim; Sivasakthya Mohan; Shanmukh Kutagulla; Matthew Disiena; Sanjay K. Banerjee; Deji Akinwande (npj 2D Materials and Applications)
Abstract Two-dimensional (2D) monolayers have gained significant attention as ultrathin active layers for fabricating atomic-scale memristor (atomristor) structures due to their crystalline structures and clean surfaces. This study reports on the giant memory window performance and low power consumption of the atomristor structures using a hexagonal boron nitride (h-BN) monolayer and symmetric silver (Ag) metal electrodes through a polypropylene carbonate (PPC) assisted transfer method. The h-BN atomristor exhibits the highest memory window (~4 × 109), the lowest leakage current (~0.24 pA), and the lowest power consumption (~3 × 10−14 W) compared to the other 2D atomristors. Furthermore, the h-BN atomristor achieves significant endurances and yields of up to 10,000 switching cycles and 77%, respectively, due to the superior thermomechanical properties of the PPC support layer for transferring ultrathin and large-area h-BN monolayers. These results represent a significant step toward the realization of high-performance and energy-efficient neuromorphic computing circuits based on 2D monolayers.